Importance of the 6′‐Hydroxy Group and Its Configuration for Apramycin Activity. Issue 9 (17th July 2014) - Mandhapati, Appi Reddy; Shcherbakov, Dimitri; Duscha, Stefan; Vasella, Andrea; Böttger, Erik C.; Crich, David
Abstract A series of apramycin derivatives was prepared and investigated for antibacterial activity and the ability to inhibit protein synthesis in cell‐free translation assays. The effect of various modifications at the 6′‐ and N7′‐positions on antiribosomal activity is discussed in terms of their influence on drug binding to specific residues in the decoding A‐site. These studies contribute to the development of a structure–activity relationship for the antibacterial activity of the apramycin class of aminoglycosides and to the future design and development of more active and less toxic antibiotics.